E-Loyalty to E-Commerce Shopee : The Role of E-WOM, E-Service Quality and E-Trust - Ricky Tantowi; Cynthia Anna Wijayanti (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
In recent years, advances in information technology have revolutionized the trade sector, particularly through e-commerce platforms such as Shopee. This platform offers convenience, speed, and practicality in online shopping, attracting millions of users. However, Shopee’s long-term success depends on user loyalty, which drives repeat purchases.This study analyzes the influence of E-WOM (E-WOM), electronic service quality, and electronic trust on user loyalty in the Shopee application, with electronic satisfaction as a mediating variable. The research population consists of all Shopee users in Medan who use the app for shopping activities, with an unknown or biased population size. Using power analysis via GPower software, the minimum required sample size was determined to be 153 respondents. The results show that E-WOM has a negative but significant effect on loyalty and satisfaction, while electronic service quality significantly affects loyalty but not satisfaction. Electronic trust shows no significant impact. Electronic satisfaction is a significant mediator only in the relationship between E-WOM and loyalty. These findings suggest that the relationships among variables are complex and not entirely linear, highlighting the need for targeted strategies to strengthen user loyalty